Dietary Patterns of Children from the Amazon Region of Ecuador: A Descriptive, Qualitative Investigation - Kristin N. Murphy; Lisa K. Boyce; Eduardo Ortiz; Marcela Santos; Gloria Balseca (MDPI AG, 2023)
Many young children in Ecuador suffer from high rates of malnutrition and stunting that affect their long-term growth and development. Little is known about the dietary patterns of children from the Amazon region who experience some of the highest rates of stunting (height-for-age) within Ecuador. Semi-structured interviews were conducted with 50 mothers of young children living in the Ecuadorian Amazon. In addition to descriptions of overall dietary patterns, three themes emerged from the interviews relating to strengths mothers have in feeding their children healthy diets: knowledge, autonomous and independent children, and supportive and responsive parenting. Five themes were found relating to barriers mothers have in feeding their children healthy diets. The first four themes concerned barriers (lack of knowledge of healthy foods, lack of access to healthy foods, not enough money, and child's health) related to multidimensional poverty. All these influenced the last theme found, namely, how difficult of an eater the child was. The implications of intervention efforts to reduce undernutrition and promote children's development by building on specific family and community strengths and identified barriers are also discussed in this paper.